Can I Use AI for Second Medical Opinions? An Academic Perspective on Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Can I Use AI for Second Medical Opinions? An Academic Perspective on Digital Health The integration of Artificial Intelligence (AI) into clinical practi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning